2004
DOI: 10.1074/jbc.m313644200
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional NMR Identifies the Conformational Shift Essential for Catalytic Competence in the 60-kDa Drosophila melanogaster dUTPase Trimer

Abstract: The catalytic mechanism of dUTP pyrophosphatase (dUTPase), responsible for the prevention of uracil incorporation into DNA, involves ordering of the flexible C terminus of the enzyme. This conformational shift is investigated by multidimensional NMR on the Drosophila enzyme. Flexible segments of the homotrimer give rise to sharp resonances in the (1)H-(15)N heteronuclear single-quantum coherence (HSQC) spectra, which are clearly distinguishable from the background resonances of the well folded protein globule.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…In contrast with DUT1, we found that the purified E. coli dUTPase exhibited a very low co-operativity ( h 1.3±0.4) in the saturation experiments with dUTP (results not shown). Previous NMR experiments with the Drosophila dUTPase revealed a co-operative behaviour and ligand-induced co-operative conformational changes in this eukaryotic dUTPase too [41]. Our present results support the suggestion that eukaryotic dUTPases have acquired positive co-operativity during evolution [41].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast with DUT1, we found that the purified E. coli dUTPase exhibited a very low co-operativity ( h 1.3±0.4) in the saturation experiments with dUTP (results not shown). Previous NMR experiments with the Drosophila dUTPase revealed a co-operative behaviour and ligand-induced co-operative conformational changes in this eukaryotic dUTPase too [41]. Our present results support the suggestion that eukaryotic dUTPases have acquired positive co-operativity during evolution [41].…”
Section: Resultssupporting
confidence: 89%
“…Previous NMR experiments with the Drosophila dUTPase revealed a co-operative behaviour and ligand-induced co-operative conformational changes in this eukaryotic dUTPase too [41]. Our present results support the suggestion that eukaryotic dUTPases have acquired positive co-operativity during evolution [41]. In the presence of saturating Mg 2+ concentrations (0.5 mM), DUT1 exhibited higher activity and affinity for dUTP resulting in 20 times higher catalytic efficiency compared with dITP (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The increased polarity of the central threefold channel, which is the main structural difference between bacterial and eukaryotic dUTPases, is suggested to render the latter protein more exposed to environmental effects. This increased sensitivity to the environment is reflected not only in decreased stability, but also in ligand induced conformational changes [15], as well as in cooperativity of nucleotide binding [6,7]. It seems that increased sensitivity towards cognate ligands, presumably required in developed organisms, is coupled to some loss of protein stability.…”
Section: Discussionmentioning
confidence: 99%
“…Both constructs were expressed in Escherichia coli BL21 (DE3) Rosetta cells under similar conditions (cf. also [17,31,32]).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%